Toxic Epidermal Necrolysis Associated with Sorafenib and Tosufloxacin in a Patient with Hepatocellular Carcinoma - Choi, Mun Ki (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
This is the first case report to describe a 44-year-old woman with a history of advanced hepatocellular carcinoma who developed toxic epidermal necrolysis (TEN) clinically after taking 400 mg sorafenib (Nexavar®, BAY 43-9006) and tosufloxacin orally once per day. Both sorafenib and tosufloxacin were eventually discontinued, and the TEN resolved with corticosteroids and supportive treatment. Clinical physicians should be aware of this possible complication so that early interventions can be made.